Turning to the Right? The Impact of the "Long Crisis Decade" (2008-2019) on Right-wing Populist Vote and Attitudes in Europe - Crulli, Mirko; Viviani, Lorenzo (PARTECIPAZIONE E CONFLITTO, 2022)
This paper questions the thesis that transformations in European politics after the financial, eurozone, and migrant crises have been led by populist radical right (PRR) and left (PRL) parties and attitudes in Northwestern (NWE) and Southern (SE) Europe, respectively. Contrary to most of the literature, we claim that, although the populist radical left has grown in SE, the more significant outcome of the crises has been to push PRR parties to a similar (high) consensus in SE and NWE. We also argue that the crises facilitated the growth of PRR forces in SE more than NWE. To test this perspective, we analysed elections and citizens’ orientations towards the key issues of populism - immigration, European integration, "authoritarianism versus liberal democracy" and "state versus market" - in five NWE and four SE countries. Findings show that during the "long crisis decade" (2008-2019) there has been an alignment on right-wing populism between European regions.